Conflict of interest explains the size of student evaluation of teaching and learning correlations in multisection studies: a meta-analysis - Bob Uttl; Kelsey Cnudde; Carmela A. White (PeerJ, 2019)
We examined the associations between the size of student evaluation of teaching and learning (SET/learning) correlations and presence of several conflicts of interest (COIs) including corporate, administrative, evaluation unit, SET author, and funder interests. Our meta-analyses of SET/learning correlations reported by multisection studies show that researchers with a vested interest in finding large positive SET/learning correlations found, on average, large positive SET/learning correlations. In contrast, researchers with no identifiable COIs found that SET/learning correlations were zero or nearly zero. The largest SET/learning correlations were reported by authors with ties to SET selling corporations. Smaller but still substantial SET/learning correlations were reported by researchers with administrative assignments and by researchers in evaluation units/departments responsible for the administration of SET. Moreover, authors with the most significant COIs were publishing their studies primarily prior to 1981 whereas authors with no or less significant COIs were publishing their studies in 1981 or afterwards. Studies published prior to 1981 reported small but significant (r = .31) SET/learning correlations whereas studies published in 1981 and after reported near zero, non-significant SET/learning correlations (r = .06). The presence of COIs was associated with earlier publication date but also with smaller samples. Finally, whereas corporate, administrative, and evaluation unit authors nearly ceased publishing multisection studies on SET/learning correlations, authors from business and economics departments are now responsible for the substantial portion of newer, larger, and higher quality studies published in 1981 and after.